Pelaksanaan Perjanjian Kerjasama antar Pengusaha dengan Serikat Pekerja - Okky Faried Hidayat; Kadek Wiwik Indrayanti; Diah ayu Wisnuwardhani (Postgraduate University of Merdeka Malang, 2020)
Collective Labor Agreement (PKB) is the result of negotiations between trade unions and employers, which contains the terms of employment, rights, and obligations of both parties. PKS PT. Indolakto Pandaan for the period 2019-2021, whose content is limited in scope and regulates general matters. Employers, trade unions, and their members knowingly, have good faith and are responsible for implementing the contents of the PKS: in financial and non-financial contexts, both express and implied. Employers and workers have done this following the contents of the PKS. There are even some things that are better implemented. Entrepreneurs put forward a sense of humanity in making decisions. Workers have understood their obligations and rights. In the event of an employment problem, employers and trade unions agree to resolve the problem and always prioritize the spirit of deliberation in the bipartite cooperation institution to reach the best consensus. An agreement with upholding and respecting the values of harmonious industrial relations, following the prevailing laws and regulations in the Republic of Indonesia so that there will be no actions that harm both parties.AbstraksPerjanjian Kerja Bersama (PKB) merupakan hasil perundingan antara serikat pekerja dan pengusaha, yang memuat ketentuan kerja, hak dan kewajiban kedua belah pihak. PKS PT. Indolakto Pandaan periode 2019-2021 yang isinya dibatasi ruang lingkup dan mengatur hal-hal umum. Pengusaha, serikat pekerja dan anggotanya dengan sadar, beritikad baik dan bertanggung jawab dalam melaksanakan isi PKS: dalam konteks finansial dan non finansial, baik tersurat maupun tersirat. Pelaksanaannya telah dilakukan oleh pengusaha dan pekerja sesuai dengan isi PKB. Bahkan ada beberapa hal yang lebih baik diterapkan. Pengusaha mengedepankan rasa kemanusiaan dalam mengambil keputusan. Pekerja telah memahami kewajiban dan hak mereka. Jika terjadi masalah ketenagakerjaan, pengusaha dan serikat pekerja sepakat menyelesaikan masalah selalu mengedepankan semangat musyawarah di lembaga kerjasama Bipartit untuk mencapai mufakat yang terbaik. Kesepakatan dengan menjunjung tinggi dan menghormati nilai-nilai hubungan industrial yang harmonis, sesuai dengan peraturan perundang-undangan yang berlaku di Republik Indonesia sehingga tidak terjadi tindakan yang merugikan kedua belah pihak.DOI: https://doi.org/10.26905/mlj.v1i2.5492